Sex-Specific Brain Activations during Single-Leg Exercise - Kyoungyoun Park-Braswell; Dustin Grooms; Sandra Shultz; Louisa Raisbeck; Christopher Rhea; Randy Schmitz (North American Sports Medicine Institute, 2022)
# Background Females have an increased incidence of musculoskeletal injuries compared to males. Sex differences in neuromuscular control has been widely studied regarding the dynamics and muscle activity during preplanned movements. While muscle activation patterns and movement biomechanics are understood to differ between sexes, it is not well understood how sex influences brain activity for lower extremity movement. Since the brain plays a vital role for voluntary movement and joint stability, it is important to understand the sex differences in brain function in order to better understand neuromuscular control associated with increased musculoskeletal injury risk in female. # Hypothesis/Purpose The purpose of this study is to understand the differences in brain activation patterns between sexes during a simple active knee extension-flexion movement. It was hypothesized that females would demonstrate higher cortical activation in the somatosensory areas compared to males as a compensatory strategy. # Study Design Cross-Sectional Study # Methods Thirteen males and seventeen females who were healthy and physically active participated in this study (Male: 23.7±3.8 years, 74.5±13.5 kg, 172.3±6.4 cm; Female: 20.6±1.6 years, 65.4±12.8 kg, 163±6.1 cm). Functional magnetic resonance imaging data were obtained during a simple left knee extension-flexion exercise with their own leg weight while lying on the MRI table. The blood oxygen level dependent (BOLD) signals were compared between sexes. # Results There was significantly greater activation in the visual cortices and premotor cortex in females compared to males during the studied movement. Males demonstrated significantly greater activation in the right cerebellum. # Conclusion The results revealed sex differences in BOLD signal during simple knee extension-flexion movement. The results suggest that sex may be a biological factor in understanding brain activity associated with knee motor control. # Level of Evidence Level 3